(untitled) (Proceedings of the International Conference on Public Health, 2025)
The Covid-19 pandemic provided lesson-learnt that ineffective epidemic control was took place when it is only prioritized on individual level and disregard the regional level. This research aims to identify the regional economic characteristics as a basis to districts/cities level pandemic control. This study analyzed infection, recovery, and death cases during the peak wave of the Delta variant on 26 May to 15 July 2021. Data were collected from 128 cities/districts of Java-Bali isles. Multivariate Analysis of Variance (MANOVA) model was applied to investigate the correlation between intercorrelated health outcomes such as infection, recovery and death cases with regional economic characteristics. The results were divided into three economic characteristic domains that significantly affected the pandemic severity. Firstly, poverty characteristic as poor people density each 10.000 km2 is prevention factor for infectious cases and risk factor for recovery cases. Second, income characteristics i.e. informal worker’s income and formal worker’s wage are the predictors for pandemic severity. Informal worker’s income is risk factor for infectious and death cases, meanwhile formal worker’s is prevention factor for death case. Third, industry characteristic significantly is the predictor for infection and recovery case. Infection case could be prevented by the regional characteristics involve workforce ratio, trade and service workforce, and middle-up enterprise. Recovery case could be prevented by workforce density characteristic and more in risky by trade and service workforce, and middle-up enterprise characteristics. This research provided the basic framework to determine non-pharmaceutical interventions as pandemic countermeasures including mobility and social interaction restriction, work from home, centralized isolation facilities, and empowering hospitalization and intensive-care resources.